Migration into tourism micro-entrepreneurship – socioeconomic advancement or mobility trap?, - Trupp, Alexander * (Routledge, 2020)
The notion of tourism micro-entrepreneurship offers the prospect of self-determination, income and further career outlooks for residents. However, tourism development in Southeast Asia has also been criticised for creating uneven development and transforming host communities into passive tourees. Along the intersecting fields of tourism, migration and micro-entrepreneurship, this chapter discusses opportunities and challenges for ethnic minority souvenir vendors who moved into Thailand’s tourist areas. Ethnic minority micro-entrepreneurs can mobilise their social and cultural capital by carving out their own niches in the tourism industry. Their activities create employment for themselves and other members of their own ethnic group and – to a minor extent – can support the livelihoods of their left-behind families. Yet, the majority of Thailand’s ethnic micro-entrepreneurs in the souvenir business come from socioeconomically marginalised regions and remain at the fringes of a business niche in urban and beach-side tourism hotspots that do not offer sustainable career prospects.